Design of a grid connected photovoltaic power electronic converter - Mustafa, Mohsin Noman (UiT Norges arktiske universitet, 2017)
In this thesis, the designing of a grid-connected photovoltaic system for the power electronic laboratory of UiT- Campus Narvik has been carried out. The relevant topics and literature regarding the elements in a photovoltaic system and grid connection standards have been studied and reviewed. A system with the capacity and ratings of solar modules currently available has been designed in Simulink. The designed system in a multistage system. Perturb and Observe algorithm is used for maximum power point tracking. Boost converter is used to amplify the photovoltaic array voltage. The inverter used is a three-phase two-level inverter. The control structure for inverter is designed in synchronous reference frame. PLL extracts the necessary information of grid voltage phase. The grid has a Line to Line voltage of 400Vrms. An LCL filter is used to interconnect inverter output to the grid. After that the results of the designed simulation are discussed. Hardware specific models are then made for code generation using the Embedded Coder feature of Simulink. In the end, discussion about this thesis, conclusion and recommendations for future work are presented